A INFLUÊNCIA DA EDUCAÇÃO EM SAÚDE NO ESTILO DE VIDA E QUALIDADE DE VIDA DE MULHERES COM CÂNCER DE MAMA - AGUIAR, Letícia Campos (2024)
Introduction: The improvement or maintenance of a healthy lifestyle presupposes a set of modifiable factors. In this regard, the use of information technology and health education can contribute to the change and adoption of a healthy lifestyle. However, little is known about the effect of interventions with health education on the impact of self-awareness and self-care for a better lifestyle, and consequently, the quality of life in women with breast cancer. Objective: To analyze the effect of health education on lifestyle and quality of life in women undergoing breast cancer treatment. The hypothesis is that a health education program can improve at least two health determinants, consequently altering the lifestyle of women undergoing breast cancer treatment. Methods: A randomized clinical trial was conducted on patients undergoing breast cancer treatment (age range 18 to 59 years). The sample was distributed by simple randomization with a 1:1 allocation into two groups: the Health Education Group (HEG) and the Control Group (CG), which remained under usual care. The Health Education Group (HEG) received a 12-week intervention through health education recommendations in both face-to-face and remote modalities, using social media. The study outcomes are: Lifestyle (Individual Lifestyle Questionnaire); Quality of life (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire); Sedentary behavior and physical activity level (ActiGraph triaxial accelerometer); Eating behavior (Food Choice Questionnaire); and Self-esteem (Rosenberg Self-Esteem Scale). Assessments were conducted at baseline, after 6 weeks, and after 12 weeks. Data were analyzed using multivariate analysis (ANOVA), comparing the effects of group, time, and interaction in SPSS software version 21.0, with α=5%. Results: In terms of lifestyle, the physical activity dimension was higher for the intervention group (p=0.034). Regarding quality of life, the functional dimension was greater for the intervention group (p=0.043). Similarly, in eating behavior, the dimensions of health (p<0.001), sensory appeal (p=0.039), and familiarity (p=0.042) showed positive results for the intervention group. Regarding self-esteem, the self- confidence dimension showed significant results at 6 weeks (p=0.008) and 12 weeks (p=0.029) of the study for the intervention group. However, physical activity levels and phase angle decreased during the weeks of intervention (p<0.05). Conclusion: The results indicated a beneficial effect of health education on the variables of lifestyle and quality of life, as well as on the health determinants of eating behavior and self-esteem in the target population of the study. Only the phase angle and levels of physical activity showed inconclusive results, which encourages the need for further studies in the area of the present work. Thus, the intervention resulted in improvements in more than two health determinants in patients undergoing breast cancer treatment, demonstrating an impact on better lifestyle habits.